FIZIKALÍQ TAYARLÍQ PROCESINDE AKMEOLOGIYALÍQ QATNAS JASAWDÍŃ DIDAKTIKALÍQ TIYKARLARÍ - Utepbergenov, A.Q.; Turganbaev, M.A. (SCIENCE and SOCIETY, 2023)
The article briefly discusses the didactic foundations of the acmeological approach, aspects of acmeology, theoretical and psychological training in physical education.
Keywords: education; training; acmeology; didactics; physical culture; sport; technology; movement; active; teacher